Makna Komunikasi Antarbudaya dalam Tradisi Antar Mahar (Ampa CO’I) Pernikahan Masyarakat Donggo dan Soromandi - Isnaini, Ahad; Muksin, Nani Nurani (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This study examines the meaning of intercultural communication in the dowry tradition among the people of Donggo and Soromandi Districts, Bima Regency. This tradition includes a series of processions such as Wi'i Nggahi, Wa'a Mama, and Ampa Co'i, which are rich in cultural symbolism and social values. This study uses a descriptive qualitative approach with communication ethnography methods through observation and in-depth interviews with community leaders. The results show that communication between families at each stage of the tradition is key to creating understanding and strengthening relationships between two families from different cultural backgrounds. However, modernization has caused a shift in values ​​in the implementation of this tradition, such as reducing face-to-face interaction and flexibility in determining post-wedding residence. Despite these changes, this tradition still holds important value as a local cultural identity and heritage. Thus, preserving the symbolic values ​​and communication in this wedding tradition is essential to maintaining social harmony and enriching the cultural heritage of the Bima people amidst the changing times.